2004
DOI: 10.1177/0890334404266972
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Enterocolitis: the Evidence for Use of Human Milk in Prevention and Treatment

Abstract: Necrotizing enterocolitis (NEC) is one of the diagnoses for which donor human milk is regularly prescribed. The role of human milk in both prevention and treatment of NEC has long been recognized. Human milk, whether mother's own or donor, provides significant protection against many of the known risk factors of NECas well as therapeutic protection for the infant recovering from NEC. In the absence of mother's own milk, donor human milk could be life saving to fragile preterm infants, who are at highest risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 33 publications
(47 reference statements)
1
37
0
2
Order By: Relevance
“…Colonization of the gastrointestinal tract of the premature infant differs greatly from that of the healthy term infant [9,20] . Patterns of intestinal colonization also vary according to the type of enteral feeding [3] . The colonization of the hospitalized, premature infant gastrointestinal tract has less species diversity and fewer anaerobic species of Lactobacillus and Bifidobacterium [9,20] .…”
Section: Patent Ductus Arteriosismentioning
confidence: 99%
See 1 more Smart Citation
“…Colonization of the gastrointestinal tract of the premature infant differs greatly from that of the healthy term infant [9,20] . Patterns of intestinal colonization also vary according to the type of enteral feeding [3] . The colonization of the hospitalized, premature infant gastrointestinal tract has less species diversity and fewer anaerobic species of Lactobacillus and Bifidobacterium [9,20] .…”
Section: Patent Ductus Arteriosismentioning
confidence: 99%
“…Onset of NEC is often within the first three months of life and neonates who are of extremely low birth weight (< 1000 g) and under 28 wk gestation are the most susceptible [2] . Full term neonates account for 10% of all NEC cases while premature infants account for 90% [3] . With an incidence rate of 1%-5% for all newborns admitted to the NICU [1] , a prevalence of 7%-14% of very low birth weight infants (VLBW, 500-1500 g) [4] and a mortality rate approaching 20%-50% [5] , NEC continues to represent a significant clinical problem.…”
Section: Introductionmentioning
confidence: 99%
“…It is suspected that abnormal colonization of the gastrointestinal tract or an unfavorable balance between commensal and pathogenic bacteria is part of the pathogenesis of NEC (4)(5)(6). It has been suggested that the ability of microflora to invade the epithelium and ferment unabsorbed nutrients (7), and the colonization by various bacterial pathogens in a sufficiently vulnerable host (8) could promote the development of NEC. Bacterial colonization of the neonatal gut is influenced by factors such as gestational age, feeding, medication, and diverse environmental flora (9).…”
mentioning
confidence: 99%
“…Previous studies suggest that use of breast milk may decrease risk of NEC. [19][20][21] In 2007, Henderson et al 30 attempted a systematic review of formula and breast milk for feeding preterm or low birth weight infants. The authors found no randomized trials of formula milk versus maternal (mother's own) breast milk for preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…The use of breast milk may be a protective factor. [19][20][21] A particularly aggressive variant, necrotizing enterocolitis totalis (NEC-T), defined in our study as intestinal necrosis greater than 80%, remains largely unstudied. It has been postulated that NEC-T may represent a different category of GI disease.…”
Section: Introductionmentioning
confidence: 99%